Nitrooxidative Stress and Neuroinflammation Caused by Air Pollutants Are Associated with the Biological Markers of Neurodegenerative Diseases - Abraham Alberto Ramírez-Mendoza; María Luisa Mendoza-Magaña; Mario Alberto Ramírez-Herrera; Zamira Helena Hernández-Nazara; José Alfredo Domínguez-Rosales (MDPI AG, 2024)
Millions of people around the world are exposed to air pollutants, such as particulate matter 2.5 (PM2.5) and ozone (O3). Such exposure usually does not exclude these two types of pollutants and their harmful effects could be additive or synergistic. O3 is a highly oxidizing gas that reacts with the cellular environment just as PM2.5, triggering nitrooxidative damage. Once nitrooxidative stress overcomes the endogenous antioxidant system, an acute neuroinflammatory process is generated, and once it becomes chronic, it favors the formation of neurodegenerative disease markers. The presence of these markers becomes potentially dangerous in people who have a genetic predisposition and are at a higher risk of developing neurodegenerative diseases such as Alzheimer's and Parkinson's. Our experimental approach for nitrooxidative damage and neuroinflammation caused by air pollutants has focused on the exposure of rats to O3 in an isolated chamber. The hippocampus is the most studied brain structure because of its neuronal connectivity network with the olfactory epithelium, its weak antioxidant defense, and its fundamental roll in cognitive processes. However, other brain structures may exhibit a different degree of damage upon exposure to O3 and PM2.5, making their involvement an important factor in developing other CNS diseases. The age spectrum for augmented sensibility to air pollutants seems to mostly affect the pre-postnatal (autism spectrum) period and the elderly (neurodegenerative). Thus, a new approach could be the estimation of the damage caused by PM2.5 and O3 through a controlled exposure paradigm to determine the extent of damage caused by both pollutants.